Acute Aortic Occlusion Presenting as Flaccid Paraplegia - Ayman Kilany; Jasem Y. Al-Hashel; Azza Rady (Case Reports in Neurological Medicine)
A 67-year-old male known to be hypertensive and diabetic had a sudden onset of severe low back pain and flaccid paraplegia with no sensory level or bladder affection and the distal pulsations were felt. Acute compressive myelopathy was excluded by MRI of the dorsal and lumbar spines. The nerve conduction study and CSF analysis was suggestive of acute demyelinating polyneuropathy. The patient developed ischemic changes of the lower limb and CT angiography revealed severe stenosis of the abdominal aorta and both common iliac arteries. We emphasize the importance of including acute aortic occlusion in the differential diagnosis of acute flaccid paraplegia especially in the presence of severe back pain even if the distal pulsations were felt.